2016
DOI: 10.1136/bmjopen-2016-011175
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus among HIV-infected individuals in follow-up care at University of Gondar Hospital, Northwest Ethiopia

Abstract: ObjectiveTo assess the prevalence of diabetes mellitus (DM) and associated factors among HIV-infected adults in northwest Ethiopia.DesignHospital-based cross-sectional study.SettingHIV clinic of the University of Gondar Hospital, Ethiopia.ParticipantsAll HIV-infected adults who visited the HIV clinic from December 2013 to the end of February 2014 were the source population.MeasuresA structured and pretested questionnaire incorporating the WHO STEPwise approach was used. A multivariate logistic regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 21 publications
10
54
1
Order By: Relevance
“…However, in line with previous studies [7,8], the current finding is slightly higher than the result (12.5%) of a community based study in the study area [40]. The finding is also comparable with results of studies conducted in different countries including, 12.7% in Eastern Ethiopia [27], 17.1% in Northwest Ethiopia [41], 15.9% in Southern Ethiopia [42], 12.3% in Nigeria [19], 11.9% in Spain [43] and 13.5% in the United States [44]. However, the magnitude in this study is lower .…”
Section: Discussionsupporting
confidence: 91%
“…However, in line with previous studies [7,8], the current finding is slightly higher than the result (12.5%) of a community based study in the study area [40]. The finding is also comparable with results of studies conducted in different countries including, 12.7% in Eastern Ethiopia [27], 17.1% in Northwest Ethiopia [41], 15.9% in Southern Ethiopia [42], 12.3% in Nigeria [19], 11.9% in Spain [43] and 13.5% in the United States [44]. However, the magnitude in this study is lower .…”
Section: Discussionsupporting
confidence: 91%
“…and it was previously undiagnosed in about three quarters (74.4%). e overall prevalence of hypertension in this study was comparable to 34% prevalence reported from Southwest Ethiopia [22] but higher than that reported from studies conducted in other parts of the country, including 12.7% in Eastern Ethiopia [23], 15.9% in Southern Ethiopia [24] and 17.1% in Northwest Ethiopia [25]. Our prevalence estimate of hypertension was also comparable to studies conducted in 4…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the observed prevalence of diabetes is comparable to 8.8% prevalence report at ART clinic of Dessie Referral Hospital, northeast, Ethiopia [36], 8.5% prevalence reported at Jimma University Specialized Hospital, Southwest, Ethiopia [37] and 8% from Wolayta Sodo Hospital, Southern Ethiopia [38]. However, the prevalence in this study is slightly higher than those reported at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia (6.9%) [39] and University of Gondar Hospital, Northwest Ethiopia (5.1%) [40]. In addition, our report was higher than the reports of those studies carried out in other countries, including Uganda (4%) [41], Malawi (4.1% and 6.6%) [42,43] Zambia (5.0%) [44], but it is lower than the report of Senegal (14.5%) [45] and Tanzania (18.0%) [46].…”
Section: Discussioncontrasting
confidence: 59%